In-vitro-fractional flow reserve of coronary artery - Puan, Chuan Yee (2018)
Existing methods of measuring the level of stenosis are either not very accurate, costly or even invasive. This project involves the study of possibility in using an external setup to measure the level of stenosis. The study involves obtaining accurate CT scan models from a actual patient and integrating the setup into an existing in-Vitro flow loop that simulates the cardiovascular system in a human body. The objective of this report is to explore the possibility of performing a catheterization process externally on a in-Vitro test setup. This experiment allows us to explore the possibility of having an alternative non-invasive method of obtaining the level of stenosis in the coronary artery that could be more accurate as compared to the existing methods. The methods used in the testing involves integrating methods to attach and modify the existing in-Vitro loop to integrate the 3d printed specimen. This involves the addition of various new components and connectors to allow for the test setup to take the pressure of the water when the loop is running at 70ml/stroke. The results obtained allow us to see that it is possible to measure the pressure waveforms at both the upstream and downstream of the stenosed regions. This result shows that there is a possibility to do the catheterization process externally, and we were able to replicate the physiological waveform from this in-Vitro flow loop. The experiment has proven to be successful and future recommendations involved with replacing the 3d printed test sections with a silicone version of it to better simulate the flexible blood vessels in the human body. There will be more test conducted on the setup to further understand the various possibilities and limitations with this non-invasive testing methods.